A hematology consensus agreement on antifungal strategies for neutropenic patients with hematological malignancies and stem cell transplant recipients. Issue 3 (5th October 2012) - Girmenia, Corrado; Aversa, Franco; Busca, Alessandro; Candoni, Anna; Cesaro, Simone; Luppi, Mario; Pagano, Livio; Rossi, Giuseppe; Venditti, Adriano; Nosari, Anna Maria
Abstract: In the attempt to establish key therapy definitions and provide shared approaches to invasive fungal diseases in neutropenic patients, trials of empiric, preeemptive and targeted antifungal therapy (EAT, PAT and TAT) were reviewed, and a Consensus Development Conference Project was convened. The Expert‐Panel concurred that all antifungal treatments, including EAT, should always follow an adequate diagnostic strategy and that the standard definition of PAT may be misleading: being PAT guided by the results of a diagnostic work‐up, it should better be termed diagnostic‐driven antifungal therapy (DDAT). The Expert‐Panel agreed that radiological findings alone are insufficient for the choice of a TAT and that the identification of the etiologic pathogen is needed. The Consensus Agreement proceeded identifying which clinical and microbiological findings were sufficient to start a DDAT and which were not. Finally, an algorithm to rationalize the choice of antifungal drugs on the basis of clinical manifestations, antifungal prophylaxis, instrumental and laboratory findings was drawn up. Copyright © 2012 John Wiley & Sons, Ltd.